1981
DOI: 10.1002/hep.1840010211
|View full text |Cite
|
Sign up to set email alerts
|

Distal splenorenal shunt vs. portal-systemic shunt: Current status of a controlled trial

Abstract: A prospective controlled comparison of portal-systemic (PSS) and distal splenorenal shunts (DSRS) in cirrhotic patients who had survived hemorrhage from esophagogastric varices was undertaken 5 yr ago at five hospitals by the Boston-New Haven Collaborative Liver Group. The clinical and endoscopic criteria for massive hemorrhage were satisfied in 155 patients. Thirty-four patients were excluded, primarily because of uncontrolled hemorrhage. Thirty-four were rejected because the were poor operative risks and 21 … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
20
2
2

Year Published

1981
1981
2000
2000

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 106 publications
(26 citation statements)
references
References 28 publications
2
20
2
2
Order By: Relevance
“…The patients were included in the placebo-treated group (260 patients) of a controlled clinical trial of prednisone (10 to 15 mg daily) versus placebo in cirrhosis (14).…”
Section: Methodsmentioning
confidence: 99%
“…The patients were included in the placebo-treated group (260 patients) of a controlled clinical trial of prednisone (10 to 15 mg daily) versus placebo in cirrhosis (14).…”
Section: Methodsmentioning
confidence: 99%
“…A preliminary report of a randomized study which compared DSRS with mesocaval and mesorenal shunts was published in 1976 by Galambos, Warren and their colleagues, and appeared to confirm the beneficial effects of the DSRS (7)(8)(9). Our preliminary report, published in 1981, suggested that although the PCA and DSRS could be performed with similar operative mortality and resulted in similar reductions in recurrent hemorrhage and in similar long-term survival, the prevalence of PSE was not decreased by DSRS (10). Four additional, controlled comparisons of DSRS and PSS have since been reported with conflicting results…”
mentioning
confidence: 89%
“…26 Thomas (1994) demonstrou que, após três anos da cirurgia, houve desaparecimento das varizes no estômago e no esôfago, demonstrando que essa técnica foi eficaz no controle do sangramento. 27 Entretanto, alguns estudos mostram que a ERD associa-se a maior incidência de encefalopatia e ressangramento do que as anastomoses porto-cava calibradas, 26 enquanto outros trabalhos não demonstraram essa relação em uma comparação entre as mesmas técnicas.…”
Section: Tabelaunclassified
“…26 Thomas (1994) demonstrou que, após três anos da cirurgia, houve desaparecimento das varizes no estômago e no esôfago, demonstrando que essa técnica foi eficaz no controle do sangramento. 27 Entretanto, alguns estudos mostram que a ERD associa-se a maior incidência de encefalopatia e ressangramento do que as anastomoses porto-cava calibradas, 26 enquanto outros trabalhos não demonstraram essa relação em uma comparação entre as mesmas técnicas. 5,28 Na comparação entre os dois procedimentos, demonstrou-se que, em um acompanhamento a longo prazo de pacientes com esquistossomose submetidos a tratamento com três diferentes abordagens, a encefalopatia por disfunção hepática e a mortalidade foram significativamente maiores na ERP quando comparada à ERD, tornando esse procedimento proibitivo em pacientes com esquistossomose.…”
Section: Tabelaunclassified